Evaluation of a Method for Biopsy of the Distal Radial Physeal Growth Plate in Neonatal Foals - Pearce, S. G.; Firth, E. C.; Hunt, W. F. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
A technique was devised for taking biopsies from the distal radial physeal growth plate in neonatal foals to study cartilage morphology. The biopsy taken from the right forelimb of 21 Thoroughbred foals, four to 10 days of age, was performed under inhalation anaesthesia, using a 9 mm diameter trephine on a multi speed drill. Due to their exercise not being adequately restricted postoperatively, five foals (24%) developed excessive incisional granulation tissue at the biopsy site. Nine foals (43%) developed some flexion of the carpus (over at the knee) and 15 (71%) developed outward rotation of the left limb. There was significantly greater carpal valgus in the left limb when compared with the right limb (p <0.005), a situation which was not present in six agematched, unoperated, control foals. Abnormalities in the congruency of the antebrachiocarpal joint were not detected grossly at postmortem at five months of age. However, there were localised gross and histological abnormalities of the distal radial physeal growth plate. Postoperative morbidity, significant changes to conformation, and the unknown long term consequences of the disruption to the biopsied physeal growth plate are likely to make this procedure inappropriate for clinical usage. However, the biopsy procedure was easy to perform, and provided a suitable sample for both histological and histomorphometric examination of the physeal growth plate cartilage. Therefore this technique provides a useful research method for study of growth plate morphology in neonates.A technique was developed for biopsy of the distal radial physeal growth plate in neonatal foals. Additionally, the effects on conformation, and on gross and histological abnormalities at five months of age, were reported. There were significant, mild conformational abnormalities, which self-corrected without intervention, and there were abnormalities detected at postmortem examination, but these abnormalities did not appear to affect the joint. The expected effects of this procedure are stated, and provided that these are accounted for, the technique is useful for harvesting and studying the physeal growth plate of neonates.
Keywords: Biopsy; physeal growth plate; conformation; foal